Cement-based capillary crystalline waterproof coating, and preparation and application thereof
By adding maleic anhydride-grafted SBS microspheres and polyether epoxy-co-modified silicone oil composite toughening agent to cement-based permeable crystalline waterproof coating, the problem of poor coating ductility is solved, and better stress absorption and waterproof performance is achieved.
Patent Information
- Application Number
- CN202411639989.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-28
AI Technical Summary
Cement-based permeable crystalline waterproof coating has poor ductility and cannot effectively absorb and disperse stress, resulting in easy breakage and affecting waterproof function.
A toughening agent composed of maleic anhydride grafted SBS microspheres and polyether epoxy co-modified silicone oil is added to the cement-based permeable crystalline waterproof coating. The flexibleness of maleic anhydride grafted SBS microspheres and the adhesion and cross-linking network structure of polyether epoxy co-modified silicone oil are improved.
It effectively improves the ductility of waterproof coatings, can absorb and disperse external forces, avoid breakage, and enhances the stress resistance and waterproof function of the coatings.
Smart Images

Figure BDA0005138174200000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of waterproof coatings, and in particular relates to a cement-based penetrating crystalline waterproof coating, and its preparation and application. Background Art
[0002] Due to the porous structure of concrete, water and other harmful ions will penetrate into it through the pores, causing its durability to decline, affecting its service life and increasing the cost of later maintenance. Penetrating crystalline waterproof coating is an inorganic rigid waterproof material made of cement as the main film-forming substance, active chemical substances as the core component, and supplemented with other components such as sand and mineral admixtures. It can be directly applied to the surface of the building. It has the advantages of good waterproof and anti-seepage properties, good impact and wear resistance, and low cost. It is widely used in roads, underground projects, and building houses.
[0003] For example, the patent CN109704661B discloses a cement-based penetrating crystallization waterproof coating, which is prepared from the following raw materials in weight ratio: cement 45-65%, quartz sand 30-40%, cellulose 0.1-0.3%, fluorosilicic acid 0.3-0.5%, complexing agent 0.02-0.05%, silica fume 0.2-0.5%, talc 2-4%, catalyst 0.05-0.08%, crystallization aid 0.1-0.12%, calcium stearate 0.01-0.02%, micro-expansion agent 0.05-0.08%, binder 0.1-0.5%, double-fast cement 5-8%, affinity agent 0.09-0.28%, and penetrant 1-2%. Patent CN101891432B discloses a penetrating crystalline waterproof coating, which is prepared by the following components in weight percentage: silicate cement: 30%-65%, quartz sand: 24%-36%, filler: 5%-16%, calcium ion compound: 1%-4%, crystallization precipitant 1.5%-4%, complexing agent 1.5%-3%, film-forming agent 1%-3%, complexing agent 0.4%-1.6%, polycarboxylic acid water reducer 0.4%-2%, and methyl cellulose 0.2%-0.4%.
[0004] The above is a penetrating crystallization waterproof coating formulated using a crystallization or precipitation mechanism. After the active ingredients in the coating penetrate into the interior of the coated substrate through water, they react and produce crystals, which can automatically repair micro cracks and have excellent performance in preventing water penetration. Although this waterproof coating has high strength and packing density after solidification, the rigid waterproof coating has poor ductility. When buildings or infrastructure are affected by factors such as temperature changes, physical loads or foundation settlement, that is, when the material produces stress, this waterproof coating cannot absorb and disperse the stress well, and is prone to breakage, which seriously affects the waterproof function.
[0005] Therefore, it is necessary to develop a cement-based penetrating crystalline waterproof coating with high ductility to resist the influence of environmental changes and substrate deformation. Summary of the invention
[0006] In order to solve the problem of poor ductility of cement-based penetrating crystalline waterproof coating, the present invention provides a cement-based penetrating crystalline waterproof coating, preparation and application thereof. A toughening agent formed by compounding maleic anhydride-grafted SBS microspheres and polyether epoxy co-modified silicone oil is added to the waterproof coating. The maleic anhydride-grafted SBS microspheres maintain the flexibility and elasticity of SBS. When the waterproof coating is solidified, the maleic anhydride-grafted SBS microspheres can absorb and disperse external forces well to avoid fracture and improve the ductility of the coating. The polar epoxy end on the polyether epoxy co-modified silicone oil has good adhesion to cement particles, fly ash, silica fume and the like, and can react with the maleic anhydride groups on the surface of the maleic anhydride-grafted SBS microspheres to form a cross-linked network structure in the solidified waterproof coating, and cooperate with the maleic anhydride-grafted SBS microspheres to improve the ductility of the coating.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] A cement-based penetrating crystalline waterproof coating comprises the following raw materials in parts by weight: 40-50 parts of silicate cement, 20-30 parts of quartz sand, 1-3 parts of alkali activator, 10-15 parts of fly ash, 10-15 parts of silica fume, 4-8 parts of toughening agent, and 0.1-0.3 parts of water reducer; the toughening agent is prepared by combining maleic anhydride grafted SBS microspheres and polyether epoxy co-modified silicone oil in a mass ratio of 3-5:0.8-1.5; the average particle size of the maleic anhydride grafted SBS microspheres is 50-100 μm.
[0009] The maleic anhydride grafted SBS microspheres are prepared by solution graft polymerization of maleic anhydride as a grafting monomer and linear SBS under the action of an initiator and then by a solvent volatilization method.
[0010] In the linear SBS, the structural unit represented by styrene accounts for 28-40wt%, the melting index under the condition of 200°C / 5kg is 3-6g / 10min; the mass ratio of SBS to maleic anhydride is 100:10-15.
[0011] The solvent volatilization method is to add an oil phase containing maleic anhydride grafted SBS to a water phase containing a surfactant, volatilize the organic solvent in the oil phase through emulsification, stirring, and freeze drying; the volume ratio of the oil phase to the water phase is 1:5-10; the concentration of maleic anhydride grafted SBS in the oil phase is 10-15wt%; the concentration of the surfactant in the water phase is 0.5-2wt%; the surfactant is selected from one or a combination of two or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate.
[0012] Specifically, the maleic anhydride grafted SBS microspheres are prepared by a method comprising the following steps:
[0013] S1) In an inert atmosphere, linear SBS and maleic anhydride are dissolved in an organic solvent, the temperature is raised, an initiator solution is added dropwise, and the reaction is carried out at a constant temperature after the addition is completed. After the reaction is completed, the reaction is distilled under reduced pressure, extracted, and dried to obtain maleic anhydride-grafted SBS;
[0014] S2) dissolving the maleic anhydride grafted SBS in an organic solvent to obtain an oil phase, dispersing a surfactant in water to obtain an aqueous phase, adding the oil phase to the aqueous phase, stirring at a high speed, heating, stirring at a low speed, centrifuging, washing, and freeze-drying to obtain the maleic anhydride grafted SBS microspheres.
[0015] In step S1), the organic solvent is selected from one or a combination of two or more of 1,2-dichloroethane, 1,2-dichloromethane, n-hexane, chloroform, benzene, tetrahydrofuran, carbon tetrachloride, toluene, and xylene. The temperature is raised to 60-80°C. The initiator solution is a mixture of an initiator and the aforementioned organic solvent, and the concentration is 2-10wt%. The amount of the initiator is 1-3wt% of the mass sum of SBS and maleic anhydride. The initiator is selected from one or a combination of two or more of azobisisobutyronitrile, diisopropylbenzene peroxide, dibenzoyl peroxide, and tert-butyl peroxide. The initiator solution is dripped in 30-60min. The reaction time is 1-3h. The reduced pressure distillation is to remove the organic solvent. The extraction is to extract and remove the unreacted maleic anhydride in a Soxhlet extractor with methanol.
[0016] In step S2), the organic solvent is selected from one or a combination of 1,2-dichloromethane, chloroform, and carbon tetrachloride, and the concentration of maleic anhydride grafted SBS in the oil phase is 10-15wt%. The surfactant is selected from one or a combination of two or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate, and the concentration of the surfactant in the water phase is 1-2wt%. The volume ratio of the oil phase to the water phase is 1:5-10. The high-speed stirring speed is 800-1000r / min and the stirring time is 0.5-1.5h. The heating is raised to 40-70°C, and the low-speed stirring speed is 300-500r / min and the time is 3-5h. The washing is washed with water 1-3 times, and the freeze-drying conditions are frozen at -50°C to -15°C for 6-24h, then placed in a freeze dryer, and dried at a vacuum degree of 5Pa-80Pa for 20-28h.
[0017] The polyether epoxy co-modified silicone oil has a viscosity of 300-800 mPa·s at 25° C. and an epoxy value of 0.01-0.03 mmol / g. Specifically, the polyether epoxy co-modified silicone oil is selected from at least one of IOTA ES12K, IOTA ES9KF, and IOTA ES7KF.
[0018] Polyether epoxy co-modified silicone oil is a new type of organosilicon material synthesized by inserting polyether macromolecules and alkylene oxides into the chain segments of polymethylsiloxane macromolecules. It has the advantages of polymethylsiloxane, alkylene oxide and polyether: the polymethylsiloxane part provides low surface tension; the alkylene oxide part provides excellent epoxy active groups, which can be well combined with other active groups to enhance its adhesion; the polyether part provides good hydrophilicity and water absorption. Polyether epoxy co-modified silicone oil has two functions in cement-based penetrating crystalline waterproof coatings. On the one hand, its hydrophilic and hydrophilic properties are used to make the maleic anhydride grafted SBS microspheres dispersed evenly when the waterproof coating is applied; on the other hand, the polyether epoxy co-modified silicone oil reacts with the anhydride on the maleic anhydride grafted SBS microspheres to form a cross-linked network structure in the waterproof coating layer, which helps to improve the ductility of the waterproof coating.
[0019] The mass ratio of maleic anhydride grafted SBS microspheres to polyether epoxy co-modified silicone oil in the toughening agent is 3-5:0.8-1.5. This ratio has a great influence on the performance of penetrating crystalline waterproof coatings. Too much polyether epoxy co-modified silicone oil will delay or even hinder the penetration of the coating into the waterproof substrate, reducing the secondary impermeability of the coating to concrete. Too little polyether epoxy co-modified silicone oil will not significantly improve the ductility of the coating. Therefore, it is necessary to strictly control this ratio during the preparation process to achieve the best performance balance.
[0020] The silicate cement is silicate cement with a strength of 42.5-52.5.
[0021] The quartz sand is continuously graded within a particle size range of 10-120 meshes.
[0022] The alkali activator is water glass with a fineness modulus of 1.5-2.0.
[0023] The fly ash is selected from one of Class I fly ash, Class II fly ash, and Class III fly ash, or a combination of two or more thereof.
[0024] The SiO2 content of the silica ash is ≥95%, the volcanic ash activity index is ≥95%, and the specific surface area is ≥20000m 2 / kg, loss on ignition ≤5%.
[0025] The water reducing agent has a water reducing rate of 20-25%, and is selected from naphthalene-based water reducing agents and polycarboxylic acid-based water reducing agents, or a combination of the two.
[0026] The present invention also provides a method for preparing the cement-based permeable crystalline waterproof coating, comprising the following steps:
[0027] The silicate cement, quartz sand, alkali activator, fly ash, silica fume, toughening agent and water reducing agent are evenly mixed to obtain a cement-based penetrating crystalline waterproof coating.
[0028] The present invention also provides an application of the cement-based penetrating crystalline waterproof coating, comprising the following steps:
[0029] T1) Clean the surface of the coated substrate to ensure that there is no debris or loose sand and gravel, and moisten it with water to make the surface of the coated substrate moist and free of visible water, and prepare the pretreated surface for use;
[0030] T2) Mix cement-based penetrating crystalline waterproof coating with water evenly, apply it on the pre-treated surface, and then maintain it.
[0031] Step T2) The mass ratio of the cement-based penetrating crystalline waterproof coating to water is 1:0.3-0.5. The thickness of the wet coating applied is 0.5-3 mm.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The cement-based permeable crystallization waterproof coating of the present invention is added with a toughening agent formed by compounding maleic anhydride grafted SBS microspheres and polyether epoxy co-modified silicone oil. The maleic anhydride grafted SBS microspheres maintain the flexibility and elasticity of SBS. After the waterproof coating is solidified, the maleic anhydride grafted SBS microspheres can absorb and disperse external forces well, avoid fracture, and improve the ductility of the coating. The polar epoxy end on the polyether epoxy co-modified silicone oil has good adhesion to cement particles, fly ash, silica fume, etc., and can react with the maleic anhydride groups on the surface of the maleic anhydride grafted SBS microspheres to form a cross-linked network structure in the solidified waterproof coating, and cooperate with the maleic anhydride grafted SBS microspheres to improve the ductility of the coating. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.
[0035] Linear SBS: styrene / butadiene mass ratio is 28 / 72, melt index is 6 g / 10 min at 200°C / 5kg, purchased from Kraton, USA, brand D1102 JS.
[0036] Linear SBS: styrene / butadiene mass ratio is 40 / 60, melt index is 3 g / 10 min at 200°C / 5kg, purchased from Kraton, USA, brand D1155JOP.
[0037] Quartz sand was purchased from Fengyang Jihui Quartz Sand Co., Ltd.: 12.5 mesh quartz sand 18wt%, 25.6 mesh quartz sand 27wt%, 48 mesh quartz sand 32wt%, 105.5 mesh quartz sand 23wt%.
[0038] Water glass with a fineness modulus of 1.5 was purchased from Guangdong Zhengneng Water Glass Co., Ltd.
[0039] Grade II fly ash was purchased from Hengshui Xiangtong Logistics Co., Ltd.
[0040] Silica ash was purchased from Chengdu Huiye Silica Ash Material Co., Ltd., with SiO2 content ≥ 98%, volcanic ash activity index ≥ 98%, and specific surface area of 29000m 2 / kg, loss on ignition 1.5%.
[0041] The polycarboxylic acid-based high-efficiency water-reducing agent was purchased from BASF, with the brand name Melflux1641F and a water-reducing rate of 20%.
[0042] Polyether epoxy co-modified silicone oil IOTA ES12KF, with a viscosity of 700 mPa·s at 25°C and an epoxy value of 0.016 mmol / g, was purchased from Anhui IOTA Silicone Oil Co., Ltd.
[0043] Polyether epoxy co-modified silicone oil IOTA ES7KF, with a viscosity of 320 mPa·s at 25°C and an epoxy value of 0.030 mmol / g, was purchased from Anhui IOTA Silicone Oil Co., Ltd.
[0044] Example 1
[0045] 1) Under nitrogen atmosphere, 100 g of linear SBS (Kraton D1102 JS) and 15 g of maleic anhydride were dissolved in 290 mL of toluene, the temperature was raised to 80° C., 100 g of azobisisobutyronitrile solution (solvent: toluene) with a concentration of 2.3 wt% was added dropwise, the dropwise addition was completed for 30 min, and the reaction was carried out at a constant temperature for 3 h. After the reaction was completed, toluene was removed by vacuum distillation, unreacted maleic anhydride was removed by extraction with methanol in a Soxhlet extractor, and the mixture was dried at 60° C. to constant weight to obtain maleic anhydride-grafted SBS;
[0046] 2) The maleic anhydride grafted SBS obtained by the method of step 1) was dissolved in 1,2-dichloromethane to obtain an oil phase with a concentration of 15wt%, sodium dodecyl sulfate was dispersed in water to obtain an aqueous phase with a concentration of 2wt%, and the oil phase was added to the aqueous phase at a volume ratio of 1:10, and stirred at a high speed of 1000r / min for 0.5h, heated to 40°C, and stirred at a low speed of 500r / min for 4.5h, centrifuged, and the precipitate was washed with water for 3 times, frozen at -50°C for 20h, and then placed in a freeze dryer and dried at a vacuum degree of 20Pa for 24h to obtain maleic anhydride grafted SBS microspheres. (average particle size 22.7μm)
[0047] 3) 40g of silicate cement with a strength of 42.5, 20g of quartz sand, 3g of water glass, 15g of fly ash, 15g of silica fume, 8g of a toughening agent prepared by combining maleic anhydride grafted SBS microspheres and polyether epoxy co-modified silicone oil IOTA ES12KF in a mass ratio of 5:1.5, and 0.1g of a water reducer Melflux1641F are mixed evenly to obtain a cement-based penetrating crystalline waterproof coating.
[0048] 4) Clean the surface of the coated substrate to ensure that there is no debris or loose sand and gravel, and moisten it with water to make the surface of the coated substrate moist and free of visible water, and prepare the pretreated surface for use;
[0049] 5) Mix cement-based penetrating crystalline waterproof coating and water in a mass ratio of 1:0.4, apply it on the pretreated surface, and maintain it to obtain a waterproof coating with a thickness of 2 mm.
[0050] Example 2
[0051] The rest is the same as Example 1, except that in step 1), an equal mass of Kraton D1155JOP is used to replace Kraton D1102 JS. (average particle size 60.1 μm)
[0052] Example 3
[0053] The rest is the same as Example 1, except that in step 3), the toughening agent is prepared by mixing maleic anhydride grafted SBS microspheres and polyether epoxy co-modified silicone oil in a mass ratio of 5:0.8. (Average particle size 60.1 μm)
[0054] Example 4
[0055] The rest is the same as Example 1, except that in step 3), the toughening agent is prepared by mixing maleic anhydride grafted SBS microspheres and polyether epoxy co-modified silicone oil in a mass ratio of 3:1.5. (Average particle size 60.1 μm)
[0056] Example 5
[0057] The rest is the same as Example 1, except that in step 4), the amount of toughening agent is 4 g. (Average particle size 60.1 μm)
[0058] Example 6
[0059] The rest is the same as Example 1, except that in step 3), the polyether epoxy co-modified silicone oil IOTA ES7KF is used instead of the polyether epoxy co-modified silicone oil IOTA ES12KF with the same mass. (Average particle size 60.1 μm)
[0060] Example 7
[0061] The rest is the same as Example 1, except that in step 2), the oil phase is prepared to a concentration of 10wt%, the high-speed stirring speed before heating is 800r / min, and the stirring time is 1.5h. (Average particle size 64.9μm)
[0062] Example 8
[0063] 1) Under nitrogen atmosphere, 100 g of Kraton D1102 JS and 15 g of maleic anhydride were dissolved in 290 mL of toluene, the temperature was raised to 80° C., 100 g of azobisisobutyronitrile solution (solvent: toluene) with a concentration of 2.3 wt% was added dropwise, the dropwise addition was completed for 30 min, and the reaction was carried out at a constant temperature for 3 h. After the reaction was completed, toluene was removed by vacuum distillation, unreacted maleic anhydride was removed by extraction with methanol in a Soxhlet extractor, and the maleic anhydride-grafted SBS was obtained;
[0064] 2) The maleic anhydride grafted SBS obtained by the method of step 1) was dissolved in 1,2-dichloromethane to obtain an oil phase with a concentration of 10wt%, sodium dodecyl sulfate was dispersed in water to obtain an aqueous phase with a concentration of 1wt%, and the oil phase was added to the aqueous phase at a volume ratio of 1:5, and stirred at a high speed of 1000r / min for 0.5h, heated to 40°C, and stirred at a low speed of 500r / min for 4.5h, centrifuged, and the precipitate was washed with water 3 times, frozen at -50°C for 20h, and then placed in a freeze dryer and dried at a vacuum degree of 20Pa for 24h to obtain maleic anhydride grafted SBS microspheres. (average particle size 79.8μm)
[0065] 3) 50g of silicate cement with a strength of 42.5, 30g of quartz sand, 3g of water glass, 10g of fly ash, 10g of silica fume, 8g of a toughening agent prepared by combining maleic anhydride grafted SBS microspheres and polyether epoxy co-modified silicone oil IOTA ES12KF in a mass ratio of 5:1.5, and 0.1g of a water reducer Melflux1641F are mixed evenly to obtain a cement-based penetrating crystalline waterproof coating.
[0066] 4) Clean the surface of the coated substrate to ensure that there is no debris or loose sand and gravel, and moisten it with water to make the surface of the coated substrate moist and free of visible water, and prepare the pretreated surface for use;
[0067] 5) Mix cement-based penetrating crystalline waterproof coating and water in a mass ratio of 1:0.4, apply it on the pretreated surface, and maintain it to obtain a waterproof coating with a thickness of 2 mm.
[0068] Comparative Example 1
[0069] The rest is the same as Example 1, except that in step 3), the toughening agent is prepared by mixing maleic anhydride grafted SBS microspheres and polyether epoxy co-modified silicone oil in a mass ratio of 5:0.5. (Average particle size 55.7 μm)
[0070] Comparative Example 2
[0071] The rest is the same as Example 1, except that in step 3), the toughening agent is prepared by mixing maleic anhydride grafted SBS microspheres and polyether epoxy co-modified silicone oil in a mass ratio of 3:1.8. (Average particle size 55.7 μm)
[0072] The following performance tests were performed on the permeable crystalline waterproof coatings prepared in the above examples and comparative examples:
[0073] Particle size analysis of microspheres: Take 50 mg of maleic anhydride grafted SBS microspheres and two drops of glycerol and mix them evenly, and use a laser particle size analyzer to measure the average particle size of the microspheres.
[0074] Tensile properties: Refer to the standard GB / T 50081-2019 Test method for physical and mechanical properties of concrete to test tensile strength and elongation at break.
[0075] Seepage resistance pressure: Refer to the standard GB / T 18445-2012 cement-based penetrating crystalline waterproof material to test the concrete's seepage resistance performance.
[0076] Table 1 Performance test results
[0077]
[0078] It can be seen from Table 1 that the cement-based penetrating crystalline waterproof coating prepared by the present invention has excellent ductility and can resist the influence of changes in the external environment and changes in the substrate.
[0079] It can be seen from the elongation at break and the secondary impermeability pressure of the coating of Example 1 and Comparative Examples 1-2 in Table 1 that the proportion of polyether epoxy co-modified silicone oil in the toughening agent has a great influence on the ductility and recovery performance. Too large a proportion is not conducive to the recovery of micro-cracks in concrete, and too small a proportion has no obvious improvement on ductility.
[0080] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A cement-based penetrating crystalline waterproof coating, characterized in that: The invention comprises the following raw materials in parts by weight: 40-50 parts of silicate cement, 20-30 parts of quartz sand, 1-3 parts of alkali activator, 10-15 parts of fly ash, 10-15 parts of silica fume, 4-8 parts of toughening agent, and 0.1-0.3 parts of water reducing agent; the toughening agent is prepared by mixing maleic anhydride grafted SBS microspheres and polyether epoxy co-modified silicone oil in a mass ratio of 3-5:0.8-1.5; the average particle size of the maleic anhydride grafted SBS microspheres is 50-100 μm.
2. The cement-based penetrating crystalline waterproof coating according to claim 1, characterized in that: The maleic anhydride grafted SBS microspheres are prepared by solution grafting polymerization of maleic anhydride as a grafting monomer and linear SBS under the action of an initiator, and then by solvent volatilization.
3. The cement-based penetrating crystalline waterproof coating according to claim 2, characterized in that: In the linear SBS, the structural unit represented by styrene accounts for 28-40wt%, the melt index under the condition of 200°C / 5kg is 3-6g / 10min; the mass ratio of SBS to maleic anhydride is 100:10-15.
4. The cement-based penetrating crystalline waterproof coating according to claim 2, characterized in that: The solvent volatilization method is to add an oil phase containing maleic anhydride grafted SBS to a water phase containing a surfactant, volatilize the organic solvent in the oil phase through emulsification, stirring, and freeze drying; the volume ratio of the oil phase to the water phase is 1:5-10; the concentration of maleic anhydride grafted SBS in the oil phase is 10-15wt%; the concentration of the surfactant in the water phase is 0.5-2wt%; the surfactant is selected from one or a combination of two or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate.
5. The cement-based penetrating crystalline waterproof coating according to claim 2, characterized in that: The maleic anhydride grafted SBS microspheres are prepared by a method comprising the following steps: S1) In an inert atmosphere, linear SBS and maleic anhydride are dissolved in an organic solvent, the temperature is raised, an initiator solution is added dropwise, and the reaction is carried out at a constant temperature after the addition is completed. After the reaction is completed, the reaction is distilled under reduced pressure, extracted, and dried to obtain maleic anhydride-grafted SBS; S2) dissolving the maleic anhydride grafted SBS in an organic solvent to obtain an oil phase, dispersing a surfactant in water to obtain an aqueous phase, adding the oil phase to the aqueous phase, stirring at a high speed, heating, stirring at a low speed, centrifuging, washing, and freeze-drying to obtain the maleic anhydride grafted SBS microspheres.
6. The cement-based penetrating crystalline waterproof coating according to claim 5, characterized in that: In step S1), the organic solvent is selected from one or a combination of two or more of 1,2-dichloroethane, 1,2-dichloromethane, n-hexane, chloroform, benzene, tetrahydrofuran, carbon tetrachloride, toluene, and xylene; the initiator solution is formed by mixing the initiator with the aforementioned organic solvent, and the concentration is 2-10wt%, the amount of the initiator is 1-3wt% of the sum of the mass of SBS and maleic anhydride, and the initiator is selected from one or a combination of two or more of azobisisobutyronitrile, diisopropylbenzene peroxide, dibenzoyl peroxide, and tert-butyl peroxide.
7. The cement-based penetrating crystalline waterproof coating according to claim 5, characterized in that: In step S2), the organic solvent is selected from one or a combination of 1,2-dichloromethane, chloroform, and carbon tetrachloride, and the concentration of maleic anhydride grafted SBS in the oil phase is 10-15wt%; the surfactant is selected from one or a combination of two or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate, and the concentration of the surfactant in the aqueous phase is 1-2wt%; the volume ratio of the oil phase to the aqueous phase is 1:5-10; the high-speed stirring speed is 800-1000r / min and the stirring time is 0.5-1.5h; the temperature is raised to 40-70°C, and the low-speed stirring speed is 300-500r / min and the time is 3-5h.
8. The cement-based penetrating crystalline waterproof coating according to claim 1, characterized in that: The polyether epoxy co-modified silicone oil has a viscosity of 300-800 mPa·s at 25° C. and an epoxy value of 0.01-0.03 mmol / g; the polyether epoxy co-modified silicone oil is specifically selected from at least one of IOTA ES12K, IOTAES9KF, and IOTA ES7KF.
9. The method for preparing the cement-based penetrating crystalline waterproof coating according to any one of claims 1 to 8, characterized in that: The steps include: The silicate cement, quartz sand, alkali activator, fly ash, silica fume, toughening agent and water reducing agent are evenly mixed to obtain a cement-based penetrating crystalline waterproof coating.
10. The use of the cement-based penetrating crystalline waterproof coating according to any one of claims 1 to 8, characterized in that: The steps include: T1) Clean the surface of the coated substrate to ensure that there is no debris or loose sand and gravel, and moisten it with water to make the surface of the coated substrate moist and free of visible water, and prepare the pretreated surface for use; T2) Mix cement-based penetrating crystalline waterproof coating with water evenly, apply it on the pre-treated surface, and then maintain it. Step T2) The mass ratio of the cement-based penetrating crystalline waterproof coating to water is 1:0.3-0.5; the thickness of the wet coating applied is 0.5-3 mm.
Citation Information
Patent Citations
Permeable crystalline waterproof coating
CN101891432B
A cement-based penetrating crystalline waterproof coating
CN109704661B
Permeable crystalline waterproof coating
CN101891432A
End-capped polyether and epoxy co-modified silicone oil and preparation method thereof
CN108864430A
Regenerated warm mixing agent, asphalt mixture and preparation method of asphalt mixture
CN117326817A